Sistem Informasi Kelas Renang Berbasis Website Pada CV. Anugrah Tirta Cemerlang - Anugerah Widi (Universitas Katolik Musi Charitas, 2020)
The development of technology requires all forms of business to change its business model. Information systems in a business are needed right now. Make the company try to provide the best in terms of service by using the help of technology and information systems. In its operational activities CV. Anugrah Tirta Cemerlang currently only uses verbal and written classroom selection service methods through the forms provided. This will certainly make it difficult to see and choose the class schedule that is available because they have to wait for the admin section to look for and see the availability of classes. Based on the description the author tries to use a Class-based Pool Class Information System on CV. Anugrah Tirta Cemerlang to solve existing problems. To analyze the problem the writer uses PIECES analysis, collecting data through interviews, observations, and literacy studies. In the development of information systems the author uses iteration software development. Designing software using UML modeling. With the construction of this information system CV. Anugrah Tirta Cemerlang can obtain information on training schedules, student data, schedule changes, and student admissions, and can assess trainer performance.